Out of nowhere - Brown, Sandra, 1948- (Grand Central, 2023)
Brought together by a mass shooting at a Texas county fair, children's book author and single mother Elle Portman and high-rolling corporate consultant Calder Hudson, both fueled by revenge, search for a killer while wondering if the attraction growing between them is too painful and complicated to sustain.